2023
DOI: 10.1037/prj0000554
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and mental health: Evidence from adults with serious mental illness.

Abstract: Objective: In the United States, loneliness is increasingly becoming a public health crisis. Individuals with serious mental illness (SMI) report loneliness at rates much higher than the general population. In this secondary data analysis, we examine how subjective and objective social isolation influence perceptions of mental health and well-being. Method: Using a cross-sectional design, we conducted a multivariate hierarchical regression analysis to determine the unique influence both subjective and objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Social exclusion is one likely explanation for this disparity. Stigma is prevalent (Snethen et al, 2021), which partially explains the lower levels of community participation that people with SMI experience (Nagata et al, 2020) and greater social isolation (Jenkins et al, 2023). Furthermore, people with an SMI face challenges in maintaining social relationships resulting from disruptive life events, such as unemployment and divorce (Perry & Pescosolido, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Social exclusion is one likely explanation for this disparity. Stigma is prevalent (Snethen et al, 2021), which partially explains the lower levels of community participation that people with SMI experience (Nagata et al, 2020) and greater social isolation (Jenkins et al, 2023). Furthermore, people with an SMI face challenges in maintaining social relationships resulting from disruptive life events, such as unemployment and divorce (Perry & Pescosolido, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The isolation caused by extensive periods spent alone in their vehicles can lead to mental health issues. Jenkins et al found a significant correlation between heightened feelings of loneliness and decreased self-reported mental health ratings, along with an increased frequency of bothersome symptoms among drivers [6].…”
Section: Related Researchmentioning
confidence: 99%
“…They did not engage in online forums or even exchange text messages [12]. This isolation can increase the risk of mental health issues and bothersome symptoms [6]. To address this challenge, it is crucial to foster connections among drivers and enhance their sense of community, particularly for full-time drivers who spend a significant amount of time driving alone.…”
Section: Isolation and Mental Healthmentioning
confidence: 99%
“…Academically, I've been interested in loneliness research for about 5 years after evaluating a peer-based community mental health program for those with serious mental illness. Approximately 60% of the participants reported loneliness in that study (Jenkins et al, 2022). I wanted to learn more about why, in a model designed to increase social connectedness, so many individuals were still reporting feelings of loneliness.…”
Section: Positionalitymentioning
confidence: 99%